Characterization of a bacteriocin produced by Lactococcus lactis subsp. lactis CRL 1584 isolated from a Lithobates catesbeianus hatchery - Pasteris, Sergio Enrique (2014)
Lactococcus lactis CRL 1584 isolated from a Lithobates catesbeianus hatchery inhibits the growth of Citrobacter freundii (a bullfrog pathogen) and Listeria monocytogenes by a synergistic effect between lactic acid, hydrogen peroxide and a bacteriocin-like molecule. The chemical characterization of the bacteriocin in cell-free supernatants indicates that it has a proteinaceous nature. Hexadecane and ethyl acetate did not modify the bacteriocin activity, while 10 and 20 % (v/v) chloroform decreased the activity by 29 and 43 %, respectively. The antimicrobial peptide was heat stable since 85 % of residual activity was detected when neutralized supernatants were heated at 80 °C for 30 min. Moreover, no bacteriocin inactivation was observed when supernatants were kept at -20 °C for 3 months. The synthesis of the bacteriocin was associated with bacterial growth, highest production (2,100 AU/ml) being detected at the end of the exponential growth phase. At pH ranges of 5-6.5 and 5.0-5.5 the inhibitory molecule was stable when stored for 2 days at 4 and 25 °C, respectively. Moreover, it had a bactericidal effect on L. monocytogenes and the ultrastructural studies of pathogenic cells revealed clumping of the cytoplasmic material, increased periplasmic space and cell wall modifications. The deduced amino acid sequence of the bacteriocin was identical to nisin Z and the genetic determinants for its production are harbored in the chromosome. These results, described for the first time in L. lactis from a bullfrog hatchery, will increase knowledge of the bacteriocin under study with a view to its potential inclusion in probiotics for raniculture or biopreservatives.